The Profile of Blindness Aetiology in Children of SLB/A Denpasar - Anak Agung Ayu Sukartini Djelantik (Journal of Global Pharma Technology, 2016)
Introduction: Blindness in children is one global problem that adressed by the World Health Organization (WHO) to achieve VISION 2020 "The Right to Sight". Blindness also occurs in high prevalence in Indonesia, but study evaluating blindness in childres is rarely conducted. Thus, this study aimed to evaluate and compiled the profile of the etiology factors related to blindess in children in Denpasar, Bali. Method: An cross sectional-obervational analitic study were conducted in SLB / A Denpasar in November 2017 and the data were collected prospectively. The samples of this study were all children in SLB/A Denpasar who met the inclusion criteria. All of the data were analyzed using SPSS 17.0 Result: 37 children were enrolled in this study and consist of 23 (62%) men and 14 (38%) women. Most participants were in the range of 12-14 years old (12 [32%]) followed by 17-20 years (11 [30%]), 9-11 years old (7 [19%]), age 15-17 years (5 [14%]) and age 6-8 years (2 [5%]). According to the visual acuity (VA), the most prevalent eye condition was severe visual impairement (<6/12 – 6/18) with 12 children (32.42%) followed by blindness (VA<3/60) in 11 children (29.72%), moderate visual impairement (<6/18 – 6/60) in 11 children (29.72%) and early visual impairement (<6/12 – 6/18) in 3 children (8.11%). In terms of eye disorder, the most prevalent was ptisis bulbi 5 children (13.5%), followed by leucoma cornea in 4 children (10.8%), nystagmus and microcornea in 2 children (5.4%). The cause of blindness in children in SLB / A was papil atrophy (18.9%), ptisis bulbi (13.5%), and leucoma cornea (8.1%). The congenital cataract with nystagmus and microcornea was found in 4 childen (10.8%) while pseudofakia with PCO was found in 3 children (8.1%). Meanwhile, congenital cataract with nystagmus and microcornea was found in 2 children (5.4%). Conclusion: It can be concluded that the cause of blindness in chlidren in SLB / A were papil atrophy, congenital cataract with nystagmus and microcornea.Keywords: Blind, SLB / A, Visual Acuity, Congenital Cataract, Papil Atrophy.